Understanding conversations about alcohol between parents and their 15-17 year olds: a qualitative study - Alexandra Sawyer; Lester Coleman; Richard Cooke; Lisa Hodgson; Nigel Sherriff (BMC, 2018)
Abstract Background There is an increasing awareness that parents can play an important role in shaping their children's attitudes towards alcohol and use of alcohol. However, there has been little research exploring the conversations parents have with their children about alcohol. The present study aims to address this gap by exploring conversations between parents and their 15-17 year old children. Methods Using a cross-sectional qualitative design, recruitment took place over two phases to allow a purposive maximum variation sample of parents and young people. Sixty-four participants (n = 48 parents; n = 16 young people aged 15-17 years) took part in semi-structured interviews. The sample was diverse and included participants from throughout the United Kingdom. Thematic analysis was used to analyse the data separately for all parents and 16 matched parent-child pairs. Results The parents' findings were summarised within the following thematic areas: 1) style of conversation; 2) triggers to conversations; 3) topics conveyed during conversations; and 4) supervision of child's alcohol consumption. Most parents were comfortable talking to their children about alcohol. It was considered that open and honest conversations helped demystify alcohol for young people. Most conversations that parents had with their children were brief and informal and a wide range of triggers to these conversations were reported. There was some indication that as children got older conversations became more frequent and more focused on safety. Overall, the matched parent-child interviews were very consistent regarding levels of child drinking, conversation starters, and topics discussed. However, in some cases parents underestimated their child's need and desire for further conversations about alcohol. Conclusions Most parents felt comfortable having conversations with their older children about alcohol. However, parents also wanted more support with having these conversations, particularly about how to start a conversation and what to talk about. This study provides several recommendations to help parents have an open conversation about alcohol with their children. For example, brief, informal chats seem to be the most appropriate way of speaking to children about alcohol compared to a more formal, "sit-down" style of conversation.